Mechanical characterization of matrix-induced autologous chondrocyte implantation (MACI®) grafts in an equine model at 53 weeks. Issue 10 (16th July 2015) - Griffin, Darvin J.; Bonnevie, Edward D.; Lachowsky, Devin J.; Hart, James C.A.; Sparks, Holly D.; Moran, Nance; Matthews, Gloria; Nixon, Alan J.; Cohen, Itai; Bonassar, Lawrence J.
Abstract There has been much interest in using autologous chondrocytes in combination with scaffold materials to aid in cartilage repair. In the present study, a total of 27 animals were used to compare the performance of matrix-assisted chondrocyte implantation (MACI®) using a collagen sponge as a chondrocyte delivery vehicle, the sponge membrane alone, and empty controls. A total of three distinct types of mechanical analyses were performed on repaired cartilage harvested from horses after 53 weeks of implantation: (1) compressive behavior of samples to measure aggregate modulus (HA) and hydraulic permeability (k) in confined compression; (2) local and global shear modulus using confocal strain mapping; and (3) boundary friction coefficient using a custom-built tribometer. Cartilage defects receiving MACI® implants had equilibrium modulus values that were 70% of normal cartilage, and were not statistically different than normal tissue. Defects filled with Maix™ membrane alone or left empty were only 46% and 51–63% of control, respectively. The shear modulus of tissue from all groups of cartilage defects were between 4 and 10 times lower than control tissue, and range from 0.2 to 0.4 MPa. The average values of boundary mode friction coefficients of control tissue from all groups ranged from 0.42 to 0.52. This study represents an extensive characterization of the mechanical performance of the MACI® grafts implant in a large animal model at 53 weeks. Collectively, these data demonstrate a range of implant performance, revealing similar compressive and frictional properties to native tissue, with inferior shear properties.